Orbital Myocysticercosis different Presentation and Management in Eastern Nepal - Hamal, Diwa; Kafle, Santosh; Kafle, Prerna Arjyal; Poudyal, Prija; Lamichhane, Binaya; Limbu, Ben (Nepalese Journal of Ophthalmology, 2020)
Introduction: Ocular cysticercosis is a preventable cause of blindness. It is caused by parasitic infestation caused by the larval form of Taenia solium. Poor sanitation and improper management of food and meat products are the major causes for cysticercosis infestation. Case: Two cases of myocysticercosis presented to our hospital differently. A 12 years boy, first case presented with drooping of right eye (RE) upper lid with recurrent swelling, pain, redness with mild headache and intermittent vomiting for 1 and half months. On examination swelling of RE upper lid, mild ptosis, abaxial proptosis with restricted motility in upgaze was noted. Orbital CT (computer tomography) scan and ocular ultrasound reports showed findings suggestive of myocysticercosis of superior rectus muscle of RE. Routine microscopic examination (RME) of stool demonstrated eggs of Taenia. Complete blood count (CBC) showed eosinophilia. As a suspected case of myocysticercosis and since the patient resided at an endemic zone, empirical therapy with albendazole and steroid was started to continue for 4 weeks. After one week the patient presented with features suggestive of RE orbital cellulitis. With proper counseling about medical therapy and cyst excision, the patient recovered well with only mild RE upper lid ptosis of 2mm. The histopathological examination (HPE) of the excised cyst was suggestive of inflammatory cystic lesion. A 55 years male presented as a second case to us with gradually increasing mass in the RE lower lid with a history of pain, difficulty in opening RE and intermittent swelling of RE 2 months back. On examination RE lower lid mass with exotropia of 15 degree, mild hypertropia was noted. CT scan showed presence of cystic mass 3.5x2x1.5cm in the right orbit involving the right inferior rectus muscle, abutting and displacing the globe superolaterally. CBC showed eosinophilia. Post cyst excision patient recovered well with remaining mild restriction in infraduction most probably due to fibrosis. HPE was conclusive of cysticercus cellulosae. Both the patients improved well with no recurrence until last visit 17 months in 12 years boy and 6 months in 55 years male after which he lost to follow. Conclusion: Myocysticercosis can occur at any age. There is equal importance of clinical, radiological, microbiological and histopathological support for proper diagnosis and management of cysticercosis. Medical therapy along with surgical excision of the cyst with it’s content may be needed in the management of myocysticersosis.